2016
DOI: 10.1007/s13202-016-0287-x
|View full text |Cite
|
Sign up to set email alerts
|

Gas chromatographic analysis of whole oil samples: implications for biodegradation in the Niger Delta

Abstract: The levels of biodegradation of five whole oil samples from five oil fields in the Niger Delta were assessed using a high-resolution gas chromatography. The results show that all the samples are at different levels of degradation ranging from slight to heavy. The crude oils from Fs, Bs and Qe fields had undergone extensive to heavy degradation, while those from Ai and Ea fields had undergone slight to moderate degradation. The low paraffinic content values in the samples suggest that the nparaffins have been d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…Pr and Ph are usually regarded as biomarkers and have been used to study the geochemical properties of crude oil for decades due to their complex structures and stable chemistry [24]. Recently, these compounds, due to their high resistance to microbial degradation, have been proposed by environmental chemists for use in oil spills fingerprinting and as conserved markers for evaluating the degradation extent of spilled oil [25,26]. Fig.…”
Section: Biodegradation Of Saturated Hydrocarbons Of Heavy Oilmentioning
confidence: 99%
“…Pr and Ph are usually regarded as biomarkers and have been used to study the geochemical properties of crude oil for decades due to their complex structures and stable chemistry [24]. Recently, these compounds, due to their high resistance to microbial degradation, have been proposed by environmental chemists for use in oil spills fingerprinting and as conserved markers for evaluating the degradation extent of spilled oil [25,26]. Fig.…”
Section: Biodegradation Of Saturated Hydrocarbons Of Heavy Oilmentioning
confidence: 99%
“…Undersaturated meteoric waters preferentially remove water-soluble compounds from oil such as light aromatics (benzene and toluene; Pytlak et al 2017), which results in an increase of bitumen and heavy oil residues (Mason et al 1995;Bennet and Larter 2008). This process is known as water washing (Mode et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, Huang et al [1] suggests that biodegradation is entirely uncontrolled by present-day reservoir temperature, because not all low-temperature reservoirs contain degraded oil [2,9], and not all deep-seated reservoired petroleum are free of petroleum degraders. Consequently, residency time, together with temperature records, play significant role [1].…”
Section: Introductionmentioning
confidence: 99%
“…Biodegradation, water-washing, and fractionation are thought to be the most common petroleum alteration processes in the Niger Delta Basin [9,14,15]. These processes are considered to be widespread in the Niger Delta, a deltaic basin with complex structural/tectonic setting, amidst reports of secondary and tertiary migrations, meteoritic water incursions in shallow reservoirs [9,14,15]. Mode et al [9] and Abrakasa and Nwankwo [15] observed variable degrees of biodegradation among some crude oils sampled from different locations in the Niger Delta.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation